Sharia Banking Business Activities in Indonesia: Review of Law No. 21 of 2008 on Sharia Banking - Salsabila, Fauziyah Latiefa; Hadiyan, Edwin (Mutawasith: Jurnal Hukum Islam, 2023)
Islamic banking business activities in Indonesia currently have a significant impact. The Indonesian government has enacted Law No. 21 of 2008 on Sharia Banking, which serves as the foundation for the regulation of activities pertaining to Islamic Banking Business. The objective of this legislation is to establish a favorable environment for the operation of Sharia banking business and to integrate Sharia principles into the activities of Sharia banking. This study using normative legal research with qualitative methods. The purpose of this scholarly article is to examine the regulatory aspect of Islamic banking activities in Indonesia, explore potential innovations that can be implemented by Islamic banking, and analyze the strategies employed by Islamic banking. Consequently, it is anticipated that this study will contribute to a more comprehensive understanding of the provisions outlined in Law No. 21 of 2008 on Sharia Banking.